(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Since the outbreak of the coronavirus, the health literacy on COVID-19 became an urgent need that was taken upon libraries and library associations responsibility, in order to raising people awareness and spreading knowledge on the right methods and protective procedures. This study will spot the light on the great role of libraries and library associations and measures the level of health information literacy for the students of Library and Information Science Department in Damascus university, for they are considered to be influencers and effective specialists in society. Therefore, they are going to be responsible for raising all social categories health awareness. The study have adopted the field survey as the best way of research can be used in response with the new COVID-19 circumstances. During the second semester 2019-2020, the survey was applied by collecting data that was answered by a category of the undergraduate students of the Library and Information Science Department, who were chosen randomly. The descriptive statistics method was used in the final analysis of the collected questionnaires. The final analysis had revealed a various differences in the health information literacy on COVID-19 among students, according to the gender, secondary certificate, in addition to the scientific level and the health conditions of the students. the analysis study was concluded with the following four suggested axes: academic qualification, continuing education, the contribution of the libraries in spreading health awareness on COVID-19, and the willingness to respond to any new epidemic that may encountered.